Keanekaragaman Jenis Capung (Odonata) di Sungai Jangkok Kota Mataram - Wihardi, Andre (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2023)
Indonesia is an archipelagic country, one of the islands in Indonesia is Lombok Island. One of the cities on Lombok Island is Mataram City. In Mataram there are rivers that divide the city, one of which is the Jangkok river. In the Jangkok River there are various kinds of biodiversity, including a diversity of dragonfly species (Odonata). Dragonflies also act as bioindicators determining water quality. This research aims to identify the types and determine the diversity index of dragonflies (Odonata) in the Jangkok River, Mataram City. This type of research is exploratory descriptive. The sampling technique determined three stations (station I in Sesaot, station II in Lingsar, and station III in Dasan Agung). Identification of Dragonfly species (Odonata) was carried out at the Biology Laboratory, Mandalika University of Education by analysis using the Shannon-Wiener formula (diversity index). The research results show that station I has the highest diversity index, namely 6,122 with species found, including: Orthetrum sabina, Diplacodes trivialis, Potamarcha congener, Neurothemis terminate, Ischnura senegalensis, and Ischnura cervila.